Sequencing of human identification markers in an Uyghur population using the MiSeq FGxTM Forensic Genomics System - Halimureti Simayijiang; Niels Morling; Claus Børsting (Oxford University Press, 2020)
Massively parallel sequencing (MPS) offers a useful alternative to capillary electrophoresis (CE) based analysis of human identification markers in forensic genetics. By sequencing short tandem repeats (STRs) instead of determining the fragment lengths by CE, the sequence variation within the repeat region and the flanking regions may be identified. In this study, we typed 264 Uyghur individuals using the MiSeq FGx™ Forensic Genomics System and Primer Mix A of the ForenSeq™ DNA Signature Prep Kit that amplifies 27 autosomal STRs, 25 Y-STRs, seven X-STRs, and 94 HID-SNPs. STRinNGS v.1.0 and GATK 3.6 were used to analyze the STR regions and HID-SNPs, respectively. Increased allelic diversity was observed for 33 STRs with the PCR-MPS assay. The largest increases were found in DYS389II and D12S391, where the numbers of sequenced alleles were 3-4 times larger than those of alleles determined by repeat length alone. A relatively large number of flanking region variants (28 SNPs and three InDels) were observed in the Uyghur population. Seventeen of the flanking region SNPs were rare, and 12 of these SNPs had no accession number in dbSNP. The combined mean match probability and typical paternity index based on 26 sequenced autosomal STRs were 3.85E−36 and 1.49E + 16, respectively. This was 10 000 times lower and 1 000 times higher, respectively, than the same parameters calculated from STR repeat lengths.Highlights Sequencing data on STRs and SNPs used for human identification are presented for the Uyghur population. STRinNGS v.1.0 was used to analyze the flanking regions of STRs. The concordance between PCR-CE and PCR-MPS results was 99.86%. Detection of sequence variation in STRs and their flanking regions increased the allelic diversity.